Pengaruh Pelatihan, Kompetensi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. XYZ - Andis Setia Putri; Hendy Tannady (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of training, competence and work discipline on the performance of employees of PT. XYZ. This study uses quantitative methods. Quantitative methods include validity test, reliability test, classical assumption test, hypothesis testing through f test and t test. The data analysis technique used is multiple linear regression analysis. Samples were taken as many as 165 respondents with purposive sampling method. The measuring instrument used is a questionnaire using a Likert scale distributed via google form. The data in this study were analyzed with the help of the SPSS 16 program. The results of this study indicate that the independent variable, namely training (X1) partially has no significant effect on employee performance (Y), while the competence variable (X2) and work discipline (X3) partially have a significant effect on employee performance (Y), and then the variables of training (X1), competence (X2) and work discipline (X3) simultaneously have a significant effect on employee performance (Y) PT. XYZ.